2014
DOI: 10.3390/toxins6051575
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Localization and Comparative Ultrastructural Study of Periplocoside NW from Periploca sepium Bunge in the Midgut of the Oriental Amyworm, Mythimna separata Walker (Lepidoptera: Noctuidae)

Abstract: Periplocoside NW (PSNW) is a novel insecticidal compound isolated from the root bark of Periploca sepium Bunge and has potent stomach toxicity against some insect pests. Previous studies showed that the Mythimna separata larva is sensitive to PSNW, but the Agrotis ispilon larva is insensitive. In this study, preliminary target localization on the midgut of M. separata larvae was conducted via a fluorescence labeling technique. A comparative ultrastructural study on the effects of PSNW on the midguts of M. sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Periplocoside X ( 80 ) was confirmed to contain a 3,7-dioxy-heptulose group [46] according to its NMR spectroscopic data and by referring to periplocoside A. In Wu and co-workers’ search for insecticidal compounds from P. supium , they discovered two new glycosides, namely periplocoside P ( 81 ) and periplocoside NW ( 82 ) [47,48]. Compounds 83 – 86 are all newly found pregnane glycosides in recent ten years [18,40,43] which are different from 47 – 82 in terms of the length and constitution of the saccharide chain at C-3 or C-20.…”
Section: Chemical Constituents From the Genus Periplocamentioning
confidence: 99%
“…Periplocoside X ( 80 ) was confirmed to contain a 3,7-dioxy-heptulose group [46] according to its NMR spectroscopic data and by referring to periplocoside A. In Wu and co-workers’ search for insecticidal compounds from P. supium , they discovered two new glycosides, namely periplocoside P ( 81 ) and periplocoside NW ( 82 ) [47,48]. Compounds 83 – 86 are all newly found pregnane glycosides in recent ten years [18,40,43] which are different from 47 – 82 in terms of the length and constitution of the saccharide chain at C-3 or C-20.…”
Section: Chemical Constituents From the Genus Periplocamentioning
confidence: 99%
“…Periplocoside P (PSP), a novel compound isolated from P. sepium has high insecticidal activity (LC 50 = 110 mg·L −1 ) against Mythimna separata [ 13 ]. To determine the specific mechanism of action of periplocosides against M. separata larvae, we performed systematic research and showed that putative targets of periplocosides may exist in the brush border membrane vesicles (BBMVs) of the larvae midgut [ 13 , 14 ]. Nevertheless, the specific site of action of periplocoside compounds remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds possess a special mode of action that involves obvious swelling of the abdomen, and, thus far, no other modes of insecticidal action have been recorded [ 8 ]. Fluorescence localization analysis indicated that periplocoside NW (PSNW) can bind to the midgut cells of Mythimna separata larvae [ 9 ]. Ultrastructural observations showed that microvilli, organelle, and cytomembrane are destructed in the midgut cells of M. separata larvae [ 10 ].…”
Section: Introductionmentioning
confidence: 99%